THE EXPERIENCES OF WOMEN AND BARRIERS FOR CAREER ADVANCEMENT IN TERTIARY INSTITUTIONS IN A SOUTH AFRICAN CONTEXT (The Pretoria Student Law Review, 2021)
In 1994, South Africa became a democratic state and focused primarily on advancing and protecting human rights; however, these rights had to first be constitutionalised. As a result, the South African Constitution was adopted in 1996 with fundamental rights under its Bill of Rights, which ensures that government can be held accountable for the protection of citizens’ rights. One of the fundamental rights entrenched in the Constitution is gender equality, which aims at increasing access for women to the public sphere and opportunities. The right is supported by domestic legislation and binding international law instruments. There is, however, limited research on the lived experiences of women at various institutions in South Africa post the adoption of the various gender equality laws, prompting the question: are institutions implementing, practicing, and embracing gender equality? This article discusses the experiences of women and the challenges that they face in the education sector focusing specifically on tertiary institutions in the context of gender equality and women as staff. The article argues that although — legislatively — South Africa has committed to gender equality, by ensuring equal representation and access to opportunities for women, the challenges that women are facing in the higher institutions show that law is not enough to deal with gender equality: There is a need for government to focus on redressing the challenges that women still face in tertiary institutions.
Keywords: experiences of women; education sector; tertiary institutions; gender equality; women as staff; equal representation